PENGARUH KARBURASI DENGAN VARIASI MEDIA PENDINGIN TERHADAP MICRO STRUKTUR BAJA KARBON - Zuchry, Muhammad (MEKTEK, 2011)
Heat treatment is a process of heating and cooling of metals in the solid state to change the physicalproperties of the metal. In the metal that has undergone heat treatment process generally experience changesin the structure due to phase changes in metals in the form of grain size, crystal shape, crystal size, crystaldefects, presipitan and content of certain chemical elements. The presence of carbon steel microstructureperuahan to show a material characteristic that can determine its properties, microstructure can be known ifthe structure is viewed under a microscope metallurgy. The microstructure is known as: ferrite, ferlit,sementik (iron carbide) and austenite with certain variations depending on the level of heat treatmentexperienced